Strong strain hardening in graphene/nanotwinned metal composites revealed by molecular dynamics simulations. (1st July 2021) - Zhang, Che; Lu, Cheng; Michal, Guillaume; Li, Jiaqing; Wang, Rui
Highlights: Four types of Gr/nt-metal composites are simulated by incorporation of graphene into nt-Au, nt-Ag, nt-Al and nt-Ni matrices, respectively. Gr/nt-Au and Gr/nt-Ag composites show strong strain hardening behavior under uniaxial compression along [1 -1 -2] direction with a high orientation dependence. The formation of ultrahigh-density twins and stable wrinkling morphology of graphene results in the secondary increase of stress. There is no strain hardening in Gr/nt-Al and Gr/nt-Ni composites, as the wrinkling of graphene cannot induce the structural transition in nt-Al and nt-Ni matrices. Abstract: In the present work, four types of graphene/nanotwinned (nt) metal composites are constructed by incorporation of graphene into nt-Au, nt-Ag, nt-Al and nt-Ni matrices, respectively. Their mechanical properties and deformation behaviors are investigated by using molecular dynamics (MD) simulations. Strong strain hardening is found in both Gr/nt-Au and Gr/nt-Ag due to fast structural transition. The transition begins with the propagation of partial dislocations, followed by lattice rotation with the formation of stacking faults, finally resulting in the formation of ultrahigh-density twins with high similarity to the experimental findings. The strain-hardening behavior can only be obtained under uniaxial compression along [1 -1 -2] direction, showing a high orientation dependence. Graphene wrinkles and symmetrical lattice structure in nt-metal matrices are two key factors for a smooth structural transition with strong strain-hardening in Gr/nt-Au and Gr/nt-Ag. However, there is no strain hardening in Gr/nt-Al and Gr/nt-Ni, as the wrinkling of graphene cannot induce the nucleation of dislocations in nt-Al and nt-Ni matrices. This work provides a valuable guideline for the design and application of graphene-reinforced metal matrix composites. Graphical abstract: Image, graphical abstract